The Analysis of Oxygen Saturation Value D-Dimer Levels and the Neutrophil-Lymphocyte Ratio Toward the Death of Covid-19 Patients with Comorbid at Gambiran Hospital, Kediri - Siti Hasna Ulfiah; Yuly Peristiowati (Journal for Quality in Public Health, 2022)
There is exponential growth  of Covid-19 cases throughout the world which mean the number of people infected with the virus has increased rapidly. This study aims about saturation oxygen, and laboratory examination results like of D-dimer and Nitrofil-limfosit Ratio to predict Covid-19 severity early. One hundred-one Covid-19 died at Gambiran Hospital Kediri to positive PCR results and with Comorbidites between June-Agust 2021 were retrospectively and classified by saturation oxygen value, level of D-dimer and level of Nitrofil-limfocytes Ratio according to CT value of PCR results. Of included patients, 52 (51.5%) female gender, 32 (31.7%) age 51-60 years, 22 ( 21.8) needed ICU admission, 66 (65.3%) 1-5 days hospitalized, the most comorbidities are Diabetes Melitus ( 60.4 %), Hipertension (9,.9%), Chronic Kidney Disesases (9.9 %), Cerebro Vascular Accident (7.9 %). Mean, median and modus Saturation Oxygen, D-dimer, NLR and CT value are 85,27 %; 90%; 93 %; 3.04 mg/L; 1.5 mg/L; 10 mg/L; 11.6; 6.8; 6.4; 21.67; 20.5; 16.59, 18.6. How ever, by applying multiple regression, D-dimer showed significant effect with CT Value of PCR results with sig. .016. Not for Saturation Oxygen (sig. .104)  and NLR (sig .461). By simultant test showed Saturation oxygen, D-dimer and NLR significans effect  R .029 with R square 0.189. D-dimer level more than 3.04 mg/L could be predictors for severe COVID-19 early. COVID-19, Severity, Saturation, Oxygen, Neutrophil-lymphocyte ratio, NLR, D-dimer, CT value, PCR, comorbidities.